Traumatic thrombosis of internal carotid artery - Singh, Prakash; Rai, S; Bedi, VS; Mohan, C (Indian Journal of Neurotrauma, 2007)
27 year old soldier sustained closed head injury in a road accident. He was unconscious for about 6hr. When seen at our hospital his GCS was 15/15; normal pupil but he had left hemiplegia. Head CT scan showed a low attenuation lesion in right fronto-parietal region suggestive of infarct. A cerebral angiogram revealed right internal carotid occlusion. He was treated with unsuccessful thrombectomy and STA-MCA by pass, anti-platelet agents and improved partially. Problems of traumatic ICA thrombosis in the setting of head injury are discussed.
Keywords: Head injury; Traumatic internal carotid thrombosis